Legal Protection for Workers who are at risk of being laid off due to exposure to Covid-19: Perlindungan Hukum Bagi Tenaga Kerja yang Terancam PHK Karena Terpapar Covid-19 - Isroiyah, Nurul; Multazam, M Tanzil (Indonesian Journal of Innovation Studies, 2023)
This study aims to find answer to the problem of workers who are laid off because of illness for less than 12 mounth, Article 81 No 40 of the job Creation Law “Termination of employment carried out for reasons as reffered to in paragraph (1) is null and void by law and the employer obliged to re-employ the worker concerned”. If the company continues to lay off workers, the workers can make demands which in the lawsuit contain alternative demands, namely: demanding that they be re-employed or demanding workers’ rights in accordance with Law No.13 of 2003. This research uses qualitative research methods that study the legislation and the principles contained in the legislation. The conclusion of the study is that laypffs carried out on the grounds that workers are exposed to Covid-19 are considered ineligible in the provisions of the law, because sick workers should receive protection from the company when carrying out obligations to the company and thecompany should fulfil responsibilities by providing protection and rights to workers tied to the company.